A public and patient consultation process as an aid to design a person‐centred randomized clinical trial. (5th July 2021) - Rix, Jacqueline; Docherty, Sharon; Breen, Alexander C.; Sewell, Philip; Branney, Jonathan
Abstract: Background: Involving patients and members of the public, together with researchers, in decisions about how studies are designed and conducted can create a study that is more person‐centred. The aim of this consultation process was to explore ways of designing a study which takes the person into consideration for the randomized clinical study entitled 'Biomechanical Effects of Manual Therapy—A Feasibility Study' using the novel approach of usability testing. Design: Patient and public volunteers were sought with experience of low back pain. Volunteers were invited to participate in usability testing (a physical walkthrough) of the proposed study method. This was followed by a discussion of areas where usability testing could not be used, such as recruitment strategies, continuity of participant care and dissemination of results. Resulting feedback was considered by the research team and alterations to the original study method were incorporated, provided the research questions could be answered and were practical within the resources available. Results: Additional recruitment strategies were proposed. Alterations to the study included reduction in study time burden; completion of study paperwork in a quieter location; continuity of participant care after the study; and methods of dissemination of overall study results to participants. Conclusion: The consultation process used the unique method of usability testing, together with a post‐usability discussion, and resulted in alterations to the future study which may facilitate making it more person‐centred. Patient and Public Contribution: Patients and public developed the future study design but did not participate in manuscript preparation.